ENVIRONMENT AND LANDSCAPE – RESOURCE FOR TOURISM (PANGEEA, 2025)
Abstract: The environemtal modelling have attracted a lot of attention in the past years. Their capacity to learn non-linear relationships between an input and an output space has a lot of applications: modeling and controlling dynamic processes and systems, signal processing, pattern recognition, forecast, climate prediction etc. This paper will approach a specific area from the large field of applications: identifying and modeling of some dynamic processes like pollution and energy management. We briefly introduce a series of theoretical considerations on process modeling and then we present several results obtained by the authors in modeling, and environmental mapping of the pollution process in Zlatna region.
Keywords: environment; landscape; tourism; cartography; environmental modelling; pollution; Zlatna region